Household Drinking Water Storage Intervention to Assess its Impact on Water Quality at Mae La Temporary Shelter - Shwe, Valerie Daw Tin; Somrongthong, Ratana; Chapman, Robert Sedgwick (Journal of Chitwan Medical College, 2019)
Background: Diarrhoea cases make up nearly two-thirds of total clinic visits at Mae La temporary shelter, Thailand, 40% being under five diarrhoeal cases. The use of a safe storage container for drinking water may prevent contamination and reduce diarrhoeal disease morbidity in camp residents. The aim of this study was to evaluate the use of safe drinking water storage containers and diarrhoeal diseases in under 5 children at the Mae La temporary shelter. Methods: A randomized controlled trail was conducted in 400 households with at least one child under 5 years old over a period of four months. Intervention households received safe containers, while control households did not. Households were visited twice weekly during the three-month follow-up. Recent occurrence of diarrhoea in children under five was ascertained and residual chlorine levels in drinking water were measured. The results were analyzed by chi-square tests and survival analyses. Results: Overall, the study found a 75% reduction of under five diarrhoea in the intervention group and 3.5-times less risk than control group subjects. Key factors associated with under five diarrhoea were: study group participation, no formal education of household primary caregivers; main sources of acquired drinking water; awareness regarding tap water chlorination; length of time living in camp Conclusions: In conclusion, intervention group participants were found to experience a reduction in diarrhoea morbidity when compared to their control group counterparts. E. coli contamination of drinking water was very common, suggesting little or no protection from chlorination.